Understanding the reading habit and attitudes among the rural community in low literacy rate areas in Malaysia: Rural library perspectives. Issue 1 (4th November 2019) - Samsuddin, Samsul Farid; Mohamed Shaffril, Hayrol Azril; Bolong, Jusang; Mohamed, Nor Aini
Abstract : Purpose: The purpose of this paper is to investigate the reading habit and attitude among rural communities in the low literacy rate areas in Malaysia. Design/methodology/approach: Multi-stage cluster and simple random sampling were employed and 400 respondents who live nearby the rural library were selected. Findings: Moderate levels of reading attitude were obtained from the result of the study, in which several variables produced a significant relationship in the reading attitude (education level, household income and time spent in reading). Practical implications: Better understanding on the reading habit and attitude among rural communities could produce better information on the service provision towards the establishment of rural libraries in low literacy rate areas in Malaysia. This would also increase the utilisation of reading sources and services provided. Originality/value: The paper provides better understanding on the reading habit and attitude among the rural communities in the low literacy rate areas in using the facilities provided by the rural libraries. The findings may be useful to the rural literacy and library development community in the developing countries.